An Analysis of Educational Values in “Totto-Chan: The Little Girl at the Window” by Tetsuko Kuroyanagi Based on Paulo Freire’s Perspective - Jamaluddin Jamaluddin; Abd. Ghofur (Institut Agama Islam Negeri Madura, 2020)
The novel